Coexistence of insomnia and chronic diseases in over 60 years olds - Wolińska, Weronika; Pawlak, Iwona Ewa; Mroczek, Bożena (Family Medicine & Primary Care Review, 2016)
Background. The coexistence of several chronic physical illness worsens and the body burden older people, causing both poor health and lower quality of life. Multidisease has a significant impact on the incidence of sleep disorders, including insomnia. Objectives. The aim of this study was to determine how selected chronic diseases are related to insomnia and its severity in over 60 year old members of the University of the Third Age in Stargard. Material and methods. The research was conducted among 131 persons aged 60 years and above, including 72.52% (n = 95) women and 27.48% (n = 36) men. The mean age was 68.12 ± 6.63. The survey was used with elements of Athens Insomnia Scale (AIS ), Insomnia Severity Index (ISI ) and author’s own questionnaire with questions about taking sleeping pills. Results . The most respondents was a arterial hypertension 53.43% (n = 70) including 68.57% in women (n = 48), and 31.43% (n = 22) in men. The indicator of multidisease was a 1,25 per respondent. Insomnia was reported in persons with arterial hypertension (Chi2 = 6.256; p = 0.043), asthma and chronic obstructive (Chi2 = 22.79; p = 0.0001), atherosclerosis (Chi2 = 8.368; p = 0.015) and depression (Chi2 = 20.94; p = 0.0002). Conclusions . Insomnia in the group of members of the University of the Third Age in Stargard coexists with chronic diseases, such as hypertension, asthma/CO PD, atherosclerosis and depression.